A Different Three-Port DC/DC Converter for Standalone PV System - Nimrod Vázquez; Carlos Manuel Sanchez; Claudia Hernández; Eslí Vázquez; Luz del Carmen García; Jaime Arau (International Journal of Photoenergy)
A three-port converter suitable for standalone applications is proposed in this paper. Each port is used for specific input or output, and its functions depend on the port; they are the renewable source, the battery set, and the output port. This proposed converter is considered for standalone operation, but it is not limited to it. Not only the system is able to deliver energy independently from each input source or in a mixed way for the output, but also the battery system may be charged from the renewable source just in case it is required. The battery port is only used when it is required; this allows increasing battery lifetime. Another important feature is that, in case of a renewable source failure, the energy is automatically demanded from the battery set, like an uninterruptible power supply. The system is able to track the maximum power of the renewable source when it is required. Operation, analysis, simulation, and experimental results are described in detail.